2019
DOI: 10.1021/acscatal.9b03596
|View full text |Cite
|
Sign up to set email alerts
|

Dual Photoredox/Nickel-Catalyzed Conversion of Aryl Halides to Aryl Aminooxetanes: Computational Evidence for a Substrate-Dependent Switch in Mechanism

Abstract: A mild and direct strategy for the construction of aryl aminooxetanes has been accomplished through the synergistic combination of photoredox and nickel catalysis. This approach represents a rare example of harnessing challenging tertiary radicals in photoredox/nickel cross-coupling. Oxetanes are often employed in medicinal chemistry as carbonyl or gemdimethyl bioisosteres, but their accessibility is hampered by the lack of practical synthetic methods. The strategy reported here utilizes a readily available ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Apart from our investigation of catalytic cycles involving primary and secondary benzyl radicals, the reactivity of tertiary aminooxetanyl radicals was also studied in the photoredox/Ni dual‐catalyzed oxetanylation of aryl halides by Terrett, Huestis, and coworkers (Figure 3). 167 Similar to the previous case, both Ni(0)/Ni(II)/Ni(III) and Ni(0)/Ni(I)/Ni(III) pathways are feasible, merging in the formation of Ni(III) intermediate 14 prior to reductive elimination to afford the C(sp 3 )‐C(sp 2 ) cross‐coupling product. Interestingly, in this system Ni(0)/Ni(II)/Ni(III) pathway was found to be dominant, with the oxidative addition of aryl halides to Ni(0) 11 as the turnover‐limiting step.…”
Section: Examples Of Mechanistic Studies Of Photoredox and Nickel Dua...supporting
confidence: 61%
See 1 more Smart Citation
“…Apart from our investigation of catalytic cycles involving primary and secondary benzyl radicals, the reactivity of tertiary aminooxetanyl radicals was also studied in the photoredox/Ni dual‐catalyzed oxetanylation of aryl halides by Terrett, Huestis, and coworkers (Figure 3). 167 Similar to the previous case, both Ni(0)/Ni(II)/Ni(III) and Ni(0)/Ni(I)/Ni(III) pathways are feasible, merging in the formation of Ni(III) intermediate 14 prior to reductive elimination to afford the C(sp 3 )‐C(sp 2 ) cross‐coupling product. Interestingly, in this system Ni(0)/Ni(II)/Ni(III) pathway was found to be dominant, with the oxidative addition of aryl halides to Ni(0) 11 as the turnover‐limiting step.…”
Section: Examples Of Mechanistic Studies Of Photoredox and Nickel Dua...supporting
confidence: 61%
“…Apart from our investigation of catalytic cycles involving primary and secondary benzyl radicals, the reactivity of tertiary aminooxetanyl radicals was also studied in the photoredox/Ni dual-catalyzed oxetanylation of aryl halides by Terrett, Huestis, and coworkers (Figure 3). 167 radical 10 to Ni(0) 11 (13.9 kcal/mol vs. 11.8 kcal/mol for oxidative addition) and the high barrier for oxidative addition from Ni(I) 12. Despite such differences, the computational results suggested that the radical addition of aminooxetanyl radical 10 to Ni(II)-aryl-bromo intermediate 13 was reversible (barrier of only 6.2 kcal/mol), which is consistent with the previous findings with benzyl radicals.…”
Section: Two-component Direct Cross-couplingmentioning
confidence: 99%
“…Several spirocyclic compounds with larger ring sizes could be coupled to 3-bromopyridine to give products 4c, 4d, 5a and 5b, provided that steric hindrance was not too high (see 5c). Surprisingly, oxetanes appear to be incompatible with the reaction conditions (see 4a, 4f, 5d and 5f), despite a successful report on their decarboxylative arylation under nickel-photoredox-catalyzed conditions [19]. As this report and MacMillan's report use more basic, but less nucleophilic bases than DABCO, namely Barton's base and MTBE, the issue might come from ring opening [20,21].…”
Section: Resultsmentioning
confidence: 83%
“…In comparison to de novo synthesis, methods for chemoselective functionalization of pharmaceutically relevant compounds could provide a more straightforward and cost-effective approach to diversify molecules for lead optimization in drug discovery. , Direct functionalization of aryl C–H bonds into C–C and C–heteroatom bonds can provide efficient access to arenes with diverse structural and physiochemical properties. Additionally, an established concept in medicinal chemistry is the development and application of bioisosteres, structural motifs that mimic common functional groups that can improve druglike properties. , Recently, photoredox catalysis has emerged as a highly efficient and mild strategy for late stage diversification and access to synthetically challenging bioisosteres. …”
Section: Late-stage Functionalization Of Pharmaceutically Relevant Co...mentioning
confidence: 99%